Quality of life in cancer outpatients using the EORTC QLQ-C30 questionnaire at PKU Muhammadiyah Yogyakarta Hospital - Fitri Ayu Wahyuni; Woro Supadmi; Endang Yuniarti (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2020)
Cancer is a disease characterized by the uncontrolled growth of abnormal cells in the body, which can be treated using chemotherapy as one of the therapies. However, some of chemotherapy's main side effects, such as nausea, vomiting, and pain, are associated with decreased quality of life. The patient's quality of life is measured from several dimensions: dimensions of physical health, psychological well-being, social and environmental relationships. This study aims to describe the quality of life of cancer patients at PKU Muhammadiyah Yogyakarta Hospital. This study used a cross-sectional design with all cancer patients undergoing chemotherapy during the study period who had met the inclusion criteria. The patient's quality of life was measured using the EORTC QLQ-C30 questionnaire. The results showed the quality of life of cancer patients based on a functional scale from the domain of the social function (84.55 ± 24.54), emotional function (79.20 ± 24.08), cognitive function (77.23 ± 27.82), role function (73.98 ± 31.85), and physical function (69.43 ± 29.09), the symptom scale shortness of breath (9.75 ± 18.62), diarrhea (11.38 ± 25.39), financial constraints (23.57 ± 24.99), constipation (25.20 ± 33.15), pain (25.61 ± 30.29), nausea and vomiting (33.33 ± 28.13), insomnia (8.21 ± 41.87), fatigue (45.79 ± 29.93), and loss of appetite (48.78 ± 37.34). The highest score on the functional scale was the social function, and the lowest score was in the physical function. The highest score on the symptom scale was appetite loss, and the lowest score was the shortness of breath.